A charge na imprensa: o jornal Folha de São Paulo e o humor político (1964-1965) - Ubinski, André Gustavo (2014)
This article is a research result conducted from the newspaper Folha de São Paulo during the two first years of the Brazilian military dictatorship. The time frame aims to give visibility to the first years of the military government and the speech built by the newspaper caricature .. The newspaper Folha de São Paulo arose from the junction of three smaller titles. Therefore, the publication got a single way and the Folha became one of the greatest representatives of the national press. From the foundation of the company in 1921, several changes took place, and the caricatures as text opinion to address policy have always been used abundantly. Therefore, the importance of this type of graphic had in this journal was perceived, and it is also noticeable the construction of a discourse from these prints. Thus, based on the analysis of this art, from the Nelson Mattos Coletti and Orlando‟s drawings, the intention was to analyze the discourse of the newspaper on the national political life. The military coup that overthrew President João Goulart has brought significant changes in the political life of the country, besides being marked by a history of violence against human rights and freedom restrictions. Therefore, the participation of the Folha de São Paulo while forming public opinion has a great importance in the impressions that the press tried to pass to its readership. Thus understanding the importance of the caricature during the period of dictatorship as politically engaged discursive practice, brings this research out. The year 1964 was marked by coups and adjustments by the Constitution and the military government, the search for the organization of the country was the subject of the caricatures found in the newspaper Folha de São Paulo. The construction of the speeches that aimed at discovering ideals enemies as communists and corrupt issues were very present in the caricatures, as well as the action of the military government, shown in the Figure of Castelo Branco, as a reformer and savior of the country attended the caricatures analyzed. In 1965 the understanding of conflicts within the power and the cracks involving the coup government's has already made the Fake Democracy character appear, building an ambiguous discourse on government practices and conflicts of interest within the military government